Dietary copper intake and the prevalence of kidney stones among adult in the United States: A propensity score matching study - Zhu, Weidong; Wang, Chunying; Wu, Jianping; Chen, Shuqiu; Mao, Weipu; Chen, Yu; Chen, Ming (Frontiers in Public Health, 2022)
Background Trace metals are essential trace elements for the human body, but insufficient or excessive levels of metal ions can lead to the development of disease. The purpose of this study was to examine the relationship between dietary intake of copper and the prevalence of kidney stones in U.S. adult population. Methods We included data on dietary intake of trace metals from 28,623 adult participants in the National Health and Nutrition Examination Survey (NHANES) database between 2007 and 2018. Multivariate logistic regression and restricted cubic spline (RCS) dose-response curves were used to explore the association between trace metals and kidney stones, and 1:1 propensity score matching (PSM) was performed between the stone formers and non-stone formers to test the validity of the results. Results Dose-response curves showed a non-linear negative association between dietary copper intake and kidney stones, and an increase in copper intake reduced the risk of kidney stones. Multivariate logistic regression analysis showed that the odds ratio (95% confidence interval) for kidney stones in each quartile of copper intake compared to the lowest quartile were 0.905 (0.808–1.011, p = 0.075), 0.880 (0.785–0.987, p = 0.028) and 0.853 (0.756–0.959, p = 0.009). In addition, similar conclusions were reached after analysis of PSM in the stone formers and non-stone formers groups. Conclusion Dietary copper intake was negatively and non-linearly correlated with kidney stones, which is worthy of further research and application in clinical practice.